2015
DOI: 10.3109/08941939.2015.1088604
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Curcumin on Intestinal Damage in Cholestatic Rats

Abstract: Curcumin treatment has a protective effect against intestinal damage induced by BDL. The ability of curcumin treatment is to inhibit BDL-induced oxidative stress, apoptosis, and cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…[ 36 ] Indeed, we found the induction of apoptosis in colonic epithelium in mice from DSS group, and showed that curcumin inhibited this elevation via suppressing the caspase‐3 pathway. Comparable studies have reported that curcumin protects against oxidative stress and apoptosis in the rat intestinal mucosa after bile duct ligation [ 37 ] ; curcumin ameliorates epithelial cell apoptosis and oxidative stress in inflamed colon mucosa in a rat model of ulcerative colitis. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] Indeed, we found the induction of apoptosis in colonic epithelium in mice from DSS group, and showed that curcumin inhibited this elevation via suppressing the caspase‐3 pathway. Comparable studies have reported that curcumin protects against oxidative stress and apoptosis in the rat intestinal mucosa after bile duct ligation [ 37 ] ; curcumin ameliorates epithelial cell apoptosis and oxidative stress in inflamed colon mucosa in a rat model of ulcerative colitis. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the composition of rats and humans’ bile constituents might serve as a limitation for the extrapolation of animal data to the clinical situation. However, the BDL model has been repeatedly mentioned as an appropriate model for investigating intestinal injury and bacterial LPS translocation to the systemic circulation ( Bedirli et al., 2009 ; Lorenzo-Zuñiga et al., 2006 ; Kanter et al., 2016 ). The occurrence of oxidative stress in the intestinal tissue of human cases of cholestasis/cirrhosis also has been mentioned in previous studies ( Tsiaoussis et al., 2015 ; Assimakopoulos et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kanter et al showed that curcumin treatment has a protective effect against intestinal damage induced by bile duct ligation (BDL) where curcumin treatment inhibits BDL-induced oxidative stress, apoptosis, and cell proliferation. 96 Curcumin reduced the expression of pro-apoptotic Bax and stimulated anti-apoptotic Bcl-2 to attenuate 5-fluorouracil-induced apoptosis of intestinal epithelial cells. Consequently, curcumin significantly reversed chemotherapy-induced weight-loss, increase of serum endotoxin and damage to intestinal mucosa structure and Yao et al hypothesized that the clinical administration of Curcumin may improve chemotherapy-induced intestinal dysfunction, thus increasing the clinical efficacy of chemotherapy.…”
Section: Other Intestine-specific Effects Of Curcuminmentioning
confidence: 99%